Match-play data according to playing categories in badminton: a systematic review - Winata, Bagus; Brochhagen, Joana; Apriantono, Tommy; Hoppe, Matthias Wilhelm (Frontiers in Sports and Active Living, 2025)
IntroductionThis systematic review aimed to investigate differences in match-play data according to the five playing categories in badminton.Materials and methodsThe systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Searches were conducted on ScienceDirect, PubMed, Google Scholar, Scopus, Web of Science, and Cochrane Library databases. Studies assessing technical-tactical actions, activity profiles, or external and internal loads as match-play outcome measures according to the five playing categories in badminton were deemed eligible. Quality assessment was performed using a modified version of the AMSTAR-2 checklist to compare the outcome measures, effect sizes (ES) and associated 95% confidence intervals were calculated.ResultsOf the 12,967 studies that were identified, 34 met the eligibility criteria. Among these, 29 and five were rated as excellent and good quality, respectively. Some individual ESs of activity profiles showed up to large differences (ES ≤ 4.52) favouring the men's compared with the women's singles category. Some individual ESs of activity profiles showed up to large differences (ES ≤ -2.72) favouring the women's doubles category compared with other doubles categories. The overall ESs for the activity profiles were large (ES = −0.76 to −0.90), favouring the doubles over the singles categories in both sexes.DiscussionThere are up to large differences in match-play data according to the five playing categories in badminton, each category placing specific demands on the players. Thus, each category requires specific training and testing procedures, what should be considered by scientists and coaches.